Αξιολόγηση ικανοποίησης οικογενειών και επαγγελματιών υγείας από την παροχή τηλεϊατρικών υπηρεσιών σε παιδιά και εφήβους με ειδικές ανάγκες φροντίδας - Φελλάς, Αντρέας (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Introduction : in the 21st century technology has evolved rapidly and has managed to eliminate distances. This has helped a lot in the health sector. Telemedicine or telehealth are examples of this new kind of services. A department that is in need of these services is the paediatrician, especially the children with chronic diseases or some kind of disabilities like special needs children. The satisfactory indicator of the patients can measure the quality of these health services. Purpose: The purpose of the reviews is to see how satisfied the families and the health professionals are with the services that the telehealth has to offer to the children with special needs and the ones with chronic diseases. Furthermore is to identify which factors can positively influence the ones that are using the services. Sources of data and methods for the research of the Greek and International bibliography are : CINAHL, EBSCO, EMBASE, AHRQ. Evidence report, PubMed and Cochrance with the key words ‘Telemedicine’ ‘Telehealth’ ‘Telepeadiatric’ ‘Telenursing’ ‘Satisfaction’ ‘Children’ and ‘Adolescents’. Results: Based on the bibliography we have concluded that Telemedicine affects positively the families and the health professionals that are using these kinds of services. The reasons that lead to the satisfaction of people that are involved are easiest access to the health services and the savings of time and cost, but even though it has many positive effects there is also a negative problem that we must put in consideration, the technical problems of the equipment can sometimes be bothersome. Conclusion : The application of Telemedicine to the health services for the children with special needs is a matter of a extreme importance, but for further research concerning the satisfaction from these kind of services in the health department it is necessary the correct application of methodology and the appropriate statistic indicator.
Keywords: Telemedicine; Medical telematics; Telenursing --Nurses’ Instruction; Adolescents